PENGARUH MEDIA PEMBELAJARAN FLASHCARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Nurul Aulia Listya Mastuti; Rarasaning Satianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Flashcard media is one of the learning media that can generate enthusiasm, student motivation, and can present something abstract into concrete, train memory, and improve students' vocabulary mastery. With several advantages of flashcard media that have been explained, researchers are interested in conducting similar research to see how flashcard media affects students' early reading skills. The use of flashcard media can later generate motivation in learning to read because it can be used through games. The method used by researchers is to use quantitative methods. The purpose of this study was to determine the effect of flashcard learning media on the early reading skills of grade I in Elementary School. The results of this study indicate that, class IB students totaling 28 students consisting of a control class without using Flashcard media while class IA totaling 28 students as an experimental class using Flashcard media. This study was conducted 1 time treatment in the experimental class and control class with the same material, namely fraction material. The control class was held on June 4, 2024 and the experimental class was held on June 3, 2024. The data needed in this study was obtained.